Upaya Meningkatkan Hasil Belajar Kimia Materi Struktur Atom melalui Model Discovery Learning Siswa Kelas X-5 SMA Negeri 6 Mataram - Husniarti, Baiq Sri Ayu (Al-DYAS, 2023)
The purpose of this study was to determine the increase in learning outcomes in Chemistry on the subject of atomic structure through the Discovery Learning model for Class X-5 students of SMA Negeri 6 Mataram in the odd semester of the 2022/2023 academic year. This research method uses Classroom Action Research (CAR). The subjects of this study were all 32 students in class X-5 at SMA Negeri 6 Mataram in the odd semester of the 2022/2023 academic year. The instruments used were: observation sheets of teacher and student activities and the rubric of student creativity using percentage analysis. Based on the results of data analysis, it was obtained that: the Discovery Learning model can improve student learning outcomes in class X-5 Mataram 6 Public High School in the odd semester of the 2022/2023 school year. In the initial conditions, students who have completeness in learning Chemistry are 15 students or if the percentage is 46.88%. In the first cycle stage, there were 25 students or if the percentage was 78.13%, this proved an increase of 13.25% from the initial conditions. Then in the second cycle of students who are in complete learning Chemistry, there are 32 students or 87.50%. This proves an increase of 9.37% from cycle II.